Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1080/01926230290166788
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Carcinogenicity Studies of Chlorpromazine Hydrochloride and p-Cresidine in the p53 Heterozygous Mouse Model

Abstract: The carcinogenic potential of chlorpromazine hydrochloride, a psychotropic agent, was assessed in the p53 heterozygous mouse assay. In a 4-week dose range finding study in p53 wild-type mice, doses of 20,40, 60, and 80 mg/kg were poorly tolerated because of mortality secondary to the severe sedative and hypotensive effects of chlorpromazine. Based on 40% mortality at a dose of 20 mg/kg in the dose-range finding study, a high dose of 10 mg/kg was chosen for the 26-week carcinogenicity study in p53 heterozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…This difference could be explained by the general toxicity of the higher dose. Supporting this possibility is the study of Petruska et al (26) who reported a high mortality rate on the administration of the phenothiazine, chlorpromazine hydrochloride, at doses >20 mg/kg in mice. In another study designed to evaluate the potential chemopreventive and anti-tumor effect of phenothiazines in vivo, Azuine et al (27) showed that several phenothiazines, particularly phenoxazine, effectively inhibited tumor growth in mouse carcinogenic models.…”
Section: Discussionsupporting
confidence: 50%
“…This difference could be explained by the general toxicity of the higher dose. Supporting this possibility is the study of Petruska et al (26) who reported a high mortality rate on the administration of the phenothiazine, chlorpromazine hydrochloride, at doses >20 mg/kg in mice. In another study designed to evaluate the potential chemopreventive and anti-tumor effect of phenothiazines in vivo, Azuine et al (27) showed that several phenothiazines, particularly phenoxazine, effectively inhibited tumor growth in mouse carcinogenic models.…”
Section: Discussionsupporting
confidence: 50%
“…Chlorpromazine is a phenothiazine drug, primarily used as a psychotropic agent since the 1950's, with a low toxicity (73)(74)(75). Its toxicity has been well documented and therefore, it has been employed as a standard in toxicity assays (74)(75)(76).…”
Section: Resultsmentioning
confidence: 99%
“…The renal changes, including papillary necrosis, have been observed with p-cresidine treatment in other studies that used p53 +/− mice (Delker, Yano, and Gollapudi 2000;Petruska et al 2002). Toxic hepatopathy was recorded when any of the following changes occurred in the liver: hepatocyte hypertrophy (often centrilobular), hepatocyte necrosis, hepatocyte apoptosis, and/or hepatocyte vacuolation.…”
Section: Macroscopic Pathology and Lesionsmentioning
confidence: 96%